Droits d’usage et environnement : ce que nous enseignent les recours concernant les installations classées dans trois régions françaises - Haï Vu Pham; Philippe Jeanneaux (VertigO)
Face to the ecological crisis, societies move towards the consideration that the environment is a common good, which is used in incompatible way. When firms produce private goods, they also produce negative external effects damaging environmental common goods. In France, command and control system has longtime been used to regulate polluting facilities which could be dangerous for the environment. In juridical terms, they are Registered Environmental Facility (REF). We examine legal litigations over REF in three French regions. The REF stakeholders’ network analysis shows that the legal litigation is a relevant process to reveal defending interests at a tribunal. It also shows collective strategies and power used by stakeholders to establish new property rights. We bring the light on legal litigations and consider them as institutions which are capable to adjust national administrative regulation to local situation even though public inquiry exists.